To rearrange the formula \( S = 12lp + B \) for \( p \), we need to isolate \( p \) on one side of the equation.
-
Start with the original formula: \[ S = 12lp + B \]
-
Subtract \( B \) from both sides: \[ S - B = 12lp \]
-
Now, divide both sides by \( 12l \) to solve for \( p \): \[ p = \frac{S - B}{12l} \]
None of the options listed match \( p = \frac{S - B}{12l} \) directly, but it looks like there may be a mistake in how the question was presented with regards to the coefficient in front of \( lp \).
If you meant \( S = lp + B \), then:
-
Start with the original formula: \[ S = lp + B \]
-
Subtract \( B \): \[ S - B = lp \]
-
Divide by \( l \): \[ p = \frac{S - B}{l} \]
If you're looking for the rearranged form in the options provided, please clarify. Otherwise, the correct form derived is \( p = \frac{S - B}{12l} \) or \( p = \frac{S - B}{l} \) based on the original formula used.